Den norske cisteren - Tom Willy Rustad (Musikk og Tradisjon)
There are many astonishingly beautiful and rare citterns exhibited in Norwegian Museums. The Norwegian cittern maker Amund Hansen (1734 – ca.1812) and his signature model, wich in the corpus design combines the shape of a bell and a pear, is the most famous of them all. The citterns by Hansen are made by the highest quality of craftsmanship and esthetical details. Even though Hansens popularity was highly acclaimed in his contemporary life, there are surprisingly few people in Norway that plays the cittern today. This article focuses on the creative approach where I try to revitalize the Amund Hansen cittern as a Norwegian folk music instrument. The first part focuses on how to make two new Hansen instruments, and the need for some stabilizing improvements. And the second part presents the process where I transform fiddle repertoire from Gudbrandsdalen over to the cittern. The imitation of the stroke patterns in the fiddle bow and other idiomatic technical elements, are important in the transformation process. You can hear the recordings at: DigitaltMuseum.no, cister/audiofiles.